Efficacy and safety of phosphodiesterase type 5 inhibitors for the treatment of distal ureteral calculi of 5 to 10 mm in size: A systematic review and network meta‐analysis. Issue 5 (21st March 2019) - Li, Jia‐Kun; Qiu, Shi; Jin, Kun; Zheng, Xiao‐Nan; Tu, Xiang; Bi, Si‐Wei; Liao, Xin‐Yang; Bao, Yi‐Ge; Yang, Lu; Wei, Qiang
Abstract : To evaluate the Efficacy and safety of phosphodiesterase type 5 inhibitors as a medical therapy for distal ureteral calculi by means of a systematic review and network meta‐analysis (NMA). We searched the Embase, Medline, and the Cochrane Central Register of Controlled Trials for randomised controlled trials (RCTs) published before May, 2017. Stone passage rate as the primary outcome. We used random effects model for pairwise meta‐analyses and Bayesian random effects model for NMA. We evaluated the quality of evidence by the GRADE framework for each network estimate. Five RCTs (861 patients) comparing four different interventions. The results of NMA showed that compared with tamsulosin alone, tamsulosin combined with tadalafil group was associated with significantly higher stone passage rate (odds radio [OR] 2.55, 95% credible intervals [Crl] 1.11 to 5.89). When considering stone expulsion rate, compared with tamsulosin, silodosin was ranked best (OR 3.58, 95% Crl 1.13 to 11.91), followed by tamsulosin combined with tadalafil (OR 2.55, 95% Crl 1.11 to 5.89) and tadalafil alone (OR 1.86, 95% Crl 0.95 to 4.25). No significant difference was found considering safety profiles between any interventions. This meta‐analysis indicates that tamsulosin combined with tadalafil is an effective treatment option for ureteral stones with a low occurrence of side effects. Clinicians should take all known safety and compliance of patients into account when choosing an optimal strategy. Since sample size of included studies, further RCTs are strongly encouraged to address the clinical question.